Comparative performance analysis of mobile IPv6 protocols: special reference to simultaneous bindings - Haseeb, Shariq; Ismail, Ahmad Faris (Science Publications, 2006)
Mobile IP is the Internet Engineering Task Force (IETF) proposal to cater for All-Internet Protocol (All-IP) mobility. It forms the backbone for next generation Wireless Internet Technology to provide uninterrupted network service while on the move. Our paper conducts a performance study of the various Mobile Internet Protocol version 6 (IPv6) protocols such as Simple Mobile IPv6, Hierarchical Mobile IPv6, Fast handover Mobile IPv6, their combination and Simultaneous Bindings Mobile IPv6. The paper benchmarks the protocol variations against the standard Mobile IPv6 protocol, by studying them under Quality of Service (QoS) parameters. We propose an evaluation model containing 5 mobile nodes and then gradually (5 nodes per stage) increasing the mobile nodes to 50. The proposed network model is then simulated in an open source simulator NS-2. This paper goes further to propose the most suitable variation of the protocol to use and the challenges faced in deployment.